A Pure First Order Representation for Undamped Second Order Descriptor Systems - A. Aasaraai (Journal of Sciences, Islamic Republic of Iran)
The aim of this paper is to analyze the undamped second order descriptor systems to show the possibility of transform an undamped second order descriptor system to a pure first order descriptor system ,on different ways, while stating some of its benefits. Meanwhile we will introduce pure first order systems and undamped second order systems and indicate that under some assumptions every undamped second order descriptor system can be changed to a pure first order one.